Association between triglyceride-glucose index and risk of end-stage renal disease in patients with type 2 diabetes mellitus and chronic kidney disease - Gao, Yue-Ming; Chen, Wei-Jia; Deng, Zhen-Ling; Shang, Zhi; Wang, Yue (Frontiers in Endocrinology, 2023)
Aims: The triglyceride-glucose (TyG) index has been proposed as a novel and credible surrogate marker of insulin resistance (IR). However, its association with the risk of end-stage renal disease (ESRD) in patients with type 2 diabetes mellitus (T2DM) and chronic kidney disease (CKD) remains unclear. Accordingly, we aimed to investigate the association between the TyG index and the risk of ESRD in patients with T2DM and CKD. Methods: A total of 1,936 patients with T2DM and CKD hospitalized in Peking University Third hospital (Beijing, China) from January 2013 to December 2021 were enrolled. The TyG index was calculated as ln[fasting triglyceride (mg/dL) × fasting blood glucose (mg/dL)/2]. ESRD was defined as an estimated glomerular filtration rate < 15 mL/min/1.73 m2 or the initiation of renal replacement therapy, either dialysis or renal transplantation. Cox proportional hazard regression was used to examine the association between the TyG index and the risk of ESRD. Results: During a mean follow-up of 41 months, 105 (5.42%) participants developed ESRD. Every unit increase in TyG index was associated with hazards of 1.50 (95% confidence interval [CI] 1.17-1.93; P = 0.001) in unadjusted analysis and 1.49 (95%CI 1.12-1.99; P = 0.006) in the fully adjusted model. Restricted cubic spline analysis showed a significant positive relationship between the TyG index and the risk of ESRD. Additionally, Kaplan-Meier analysis identified significant risk stratification with a cut-off value of the TyG index be 9.5 (P = 0.003). Conclusion: An elevated TyG index was significantly and positively associated with ESRD risk in patients with T2DM and CKD. This conclusion lends support to the clinical significance of the TyG index for the assessment of renal function progression in patients with T2DM and CKD.